2017
DOI: 10.13005/ojc/330142
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Post Annealing on Antibacterial Activity of Zno thin films Prepared by Modified Silar Technique

Abstract: Zinc oxide (ZnO) thin films were prepared by modified Successive Ionic Layer Adsorption and Reaction (SILAR) method. The optical, structural and antibacterial properties of the prepared ZnO films were analyzed as a function of its annealing temperature lying in the range of 250ºC to 450ºC. Optical properties were studied using UV-Visible spectroscopy and Photoluminescence spectroscopy (PLS). Optical absorption spectra exhibited blue shift when compared to the bulk value and also the presence of interstitial Zn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…En las películas delgadas tratadas a 400 ⁰C se observa un comportamiento parecido al de las películas a 500 ⁰C donde las películas de 1 capa presentan una mayor intensidad que las de 3 capas. Existen investigaciones en la literatura que han reportado que el aumento en la temperatura de sinterización puede generar incremento en la emisión del rango verde para las películas de ZnO, debido al aumento en las vacancias de iones de oxígeno [35], las cuales coinciden con los resultados obtenidos en este trabajo, como se observa al comparar las emisiones de las películas sinterizadas a 500 ⁰C con respecto a las películas obtenidas a 400 ⁰ C, que no presentan emisión en la región cercana al verde. En la Figura 6 se presenta un diagrama esquemático de la estructura de bandas reportadas de películas delgadas de ZnO [36] y ZnO-Cu.…”
Section: Resultsunclassified
“…En las películas delgadas tratadas a 400 ⁰C se observa un comportamiento parecido al de las películas a 500 ⁰C donde las películas de 1 capa presentan una mayor intensidad que las de 3 capas. Existen investigaciones en la literatura que han reportado que el aumento en la temperatura de sinterización puede generar incremento en la emisión del rango verde para las películas de ZnO, debido al aumento en las vacancias de iones de oxígeno [35], las cuales coinciden con los resultados obtenidos en este trabajo, como se observa al comparar las emisiones de las películas sinterizadas a 500 ⁰C con respecto a las películas obtenidas a 400 ⁰ C, que no presentan emisión en la región cercana al verde. En la Figura 6 se presenta un diagrama esquemático de la estructura de bandas reportadas de películas delgadas de ZnO [36] y ZnO-Cu.…”
Section: Resultsunclassified
“…ZnO thin films were deposited on glass substrate by the modified SILAR technique [7]. For Co doping, cobalt acetate [(CH3COO) 2 Co.4H 2 O] was used along with the solute.…”
Section: Materials and Methodology A Deposition Of Thin Filmmentioning
confidence: 99%
“…The results clearly indicate that the ZnO and MgO nanoparticles inhibit the growth of both gram-negative and positive bacteria. It is found that the antibacterial activity of Gram-positive bacteria higher than Gram-negative bacteria due to the negatively charged radicals that readily adhere to the cell wall of Gram-positive bacteria and thus kill the bacteria [42]. The maximum antibacterial activity of ZnO nanoparticles was against (Enterococcus faecalis).…”
Section: Antibacterial Activity Of Zn 1-x Mg X O Nanocompositesmentioning
confidence: 99%
“…This is due to the well-established attachment of ZnO molecules to the outer cell wall membrane of bacteria. Then, the ZnO molecules start to release oxygen species into the bacteria in the medium, stopping the cell from growing, causing the cell to deform and leak, eventually killing the cell [42].…”
Section: Antibacterial Activity Of Zn 1-x Mg X O Nanocompositesmentioning
confidence: 99%